Comparison of Safety and Efficacy Between Dabigatran and Rivaroxaban in Nonvalvular Atrial Fibrillation in Tertiary Level Hospital - Ahasan, Mohammad Hasimul; Mahmood, Manzoor; Adhikary, Dipal Krishna; Ahsan, Syed Ali; Ahmed, Chaudhury Meshkat; Salim, Md Abu; Ahmed, Khurshed; Amin, Md Rasul; Khaled, Md Fakhrul Islam; Singha, Chayan Kumar; Islam, Rashedul; Ansari, Sanjida; et al. (University Heart Journal, 2022)
Background: Thromboembolism is a major complication of atrial fibrillation. Vitamin K antagonist is the main oral anticoagulant which was used for prevention of thromboembolism in atrial fibrillation for many years. New oral anticoagulant drugs are emerging as alternatives to warfarin for the prevention of stroke in patients with non-valvular atrial fibrillation. Objective: The aim of the study was to compare safety and efficacy of dabigatran and rivaroxaban for prevention of thromboembolism in tertiary level hospital. Methodology: This Randomized controlled trial study was conducted in the Department of Cardiology in Bangabandhu Sheikh Mujib Medical University, Shahbagh, Dhaka. Patients were divided into two groups, in group A 37 patients were given dabigatran 110 mg twice daily and in group B 37 patients were given rivaroxaban 20 mg daily for 6 months duration. Data was collected according to the pre designed semistructured data collection sheet. Statistical analyses were carried out by using the Statistical Package for Social Sciences (SPSS) version 23.0 for Windows Software. Results: The mean CHADS2- VASC score (Risk of stroke) in rivaroxaban group and in dabigatran group was 3.95±1.37 and 3.74±1.42 respectively. There was no significant difference of CHADS2- VASC score between the two groups. Regarding outcome of 6th month follow up 2(5.4%) patients were lost to follow up in dabigatran group and 3(8.1%) in rivaroxaban group. Comparaing effectiveness and safety study we found that ischemic stroke rate with rivaroxaban group was higher than dabigatran group although statistically not significant. We also found higher bleeding rate in rivaroxaban group than dabigatran group although statistically not significant. Conclusion: Dabigatran is a safe and effective anticoagulant same as rivaroxaban for prevention of thromboembolism in the treatment of non valvular atrial fibrillation. University Heart Journal 2022; 18(1): 10-13